Aluminium sulphate (alum) recovery by acidification on the water treatment sludge - Mohd Firdaus, Che Dolah (2006)
Aluminium sulphate (alum) is a solution added to the water to coagulate solids particles in the water. It is to make sure water that sent for domestic use is free of solids particles. This process is called coagulation process. Aluminium sulphate (alum) that coagulated with solids particles forming alum sludge. Alum sludge settles in the bottom of water treatment plant together with the solid particles. The significant of this study is to recover aluminium sulphate (alum) from alum sludge. Acidification process applied to alum sludge to recover aluminium sulphate (alum). Acidification using sulphuric acid will separate particulate solids and aluminium sulphate(alum). Aluminium sulphate (alum) will be recovered in aqueous solution, while particulate solids will remain in solid form. The research also done to obtain the optimum pH for acidification to obtain the best volume recovered of aluminium sulphate (alum). There are some other factors to recover aluminium sulphate (alum) at the optimum point that it has to do with stirring speeds and centrifugation time. These factors will give effects to the precipitation period, aluminium sulphate (alum) recovery and the percentage of aluminium recovery efficiency. From the experiments, the best volume recovered is at 2.5 of pH values, 100 rpm stirring speeds and 40 minutes centrifugation time. The result shows 89.2 ml recovered from 100 ml sample of aqueous aluminium sulphate, 16 hours precipitation period, 1.29 mg/L Al3+ recovery in the solution which brings to 39.7% efficiency of recovery.